Sport, exercise, recreation and e-sport participation in Malaysia - Aman, Mohd Salleh; Elumalai, Gunathevan; Zamri, Nur Najmin Naja; Ponnusamy, Vellapandian; Mamat, Shariffah; Sharif, Shamshuritawati; Ismail, Hashbullah; Arshad, Mohd Mursyid; Suradi, Nur Riza; Imran, Farrah Hani (Horizon Research Publishing, 2024)
The Malaysian Sports Culture Index (MSCI) is the baseline index for reporting on the achievement of Malaysians in practicing sports activities with the availability of its ecosystem. MSCI’22 is a continuation of the study which was first initiated by the Institute for Youth Research Malaysia (IYRES) in 2018. This index is the basis for the formation of the National Sports Vision 2030 and serves as a guideline for monitoring sports culture programs throughout the country. MSCI’22 succeeded in gathering 3,735 respondents from various backgrounds according to age group, gender, ethnicity, and location. In terms of location, the research used the Population Census 2020, with 720 Counting Blocks (CB) and 7200 Places of Residence (PR). The proportionate random stratified sampling method was used, and samples were taken based on the CB and PR population data of 23 million Malaysian citizens aged 13 years and above. IYRES developed a special research system (online and offline) for the purpose of data collection. The findings of the study revealed that 48 of respondents were involved in sports-related activities. Among these, only 13.6 (n = 1,781) were at the active level, while 65.7 were moderately active, and 20.7 were less active. Most Malaysians were interested in sports activities (55.5), followed by exercise (37.0) and recreation (21.6). The most popular sports activities were football (11.6), futsal (11.0), and badminton (8.5). For exercise, jogging (23.1) was the most dominant, likely because it does not require special facilities and can be done in residential areas. In terms of recreation, cycling (10.4) and hiking (6.1) were the preferred activities. The study also indicated that 22.4 of Malaysians were involved in e-sports, while 77.6 were not involved. In conclusion, several factors, such as facilities, financial support, environment, and motivation, contribute to an active lifestyle. However, the study also highlighted that self-awareness plays a crucial role in encouraging sports, exercise, and recreation participation among Malaysians. Overall, the MSCI'22 study provides valuable insights into the current state of sports culture in Malaysia and can be used to shape and improve national sports initiatives and programs.